A multilevel perspective of the identity transition to motherhood. Issue 7 (4th January 2019) - Hennekam, Sophie; Syed, Jawad; Ali, Faiza; Dumazert, Jean‐Pierre
Abstract : This study examines the identity transition of women when they become mothers and return to work. Twenty‐two first‐time mothers were interviewed at two points in time: just after giving birth and on re‐entry into employment after maternity leave. The findings suggest that this transition is influenced by multiple factors on different levels which include individual factors, such as partner support and career aspirations, organizational factors such as family‐friendly work practices and role models, and societal factors such as social norms and attitudes towards the maternal body. The findings highlight the importance of context by stressing the interrelated nature of factors on the micro‐, meso‐ and macro‐level in order to better understand the identity transition to motherhood.